Corrosion performance of austenitic stainless steel SS304 in molten nitrate salts and Raman microscopy for stability analysis in thermal energy storage applications. (15th December 2021) - Villada, Carolina; Toro, Alejandra; Bolívar, Francisco
Highlights: High-temperature corrosion behavior is analyzed for three different molten salt mixtures, including two commercial salt mixtures. LiNO3 addition in molten nitrate mixtures has a better behavior against corrosion. Melting behavior and long-term thermal stability is discussed for two commercial salt mixtures. Confirmation of the irreversible reaction of the ternary Hitec under an open-air atmosphere. Raman microscopy is an appropriate technique for the nitrate-nitrite equilibrium analysis. Abstract: In the present work, the corrosion performance of stainless austenitic steel SS304 in contact with three different molten nitrate salts was studied under long-term isothermal conditions. The microstructure and corrosion products during 2000 h corrosion test were analyzed by SEM/EDX as well as XRD after immersion in Solar Salt (60 wt.% NaNO3 - 40 wt.% KNO3 ), Hitec (7 wt.% NaNO3 – 53 wt.% KNO3 – 40 wt.% NaNO2 ) and the quaternary salt 45 wt.% KNO3 - 34 wt.% NaNO2 - 15 wt.% LiNO3 - 6 wt.% NaNO3 . Additionally, deeper analyzes with the current commercial salts were carried out in order to provide experimental data not only for the metal/salt interaction but also for the chemical interaction salt/atmosphere. The melting behavior and maximum thermal stability of Solar Salt and Hitec were analyzed by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The melting and degradation temperature are discussed as well as the thermal stability of both salts monitored by Raman microscopy, which is an appropriate technique that confirmed the equilibrium alteration by decreasing the nitrite ion content over time. This work allows us to understand not only the high-temperature corrosion behavior of a potential container material but the chemical changes and thermal stability in molten salt mixtures. The results providing here may help to improve the understanding of material compatibility as well as the optimization of the engineering design with molten salts for thermal energy storage technologies. Graphical abstract: Image, graphical abstract